Symptom trajectories in the first 18 months and autism risk in a prospective high‐risk cohort. (29th March 2021) - Zwaigenbaum, Lonnie; Brian, Jessica; Smith, Isabel M.; Sacrey, Lori‐Ann R.; Franchini, Martina; Bryson, Susan E.; Vaillancourt, Tracy; Armstrong, Vickie; Duku, Eric; Szatmari, Peter; Roberts, Wendy; Roncadin, Caroline
Abstract : Background: Although early autism spectrum disorder (ASD) detection strategies tend to focus on differences at a point in time, behavioral symptom trajectories may also be informative. Methods: Developmental trajectories of early signs of ASD were examined in younger siblings of children diagnosed with ASD ( n = 499) and infants with no family history of ASD ( n = 177). Participants were assessed using the Autism Observation Scale for Infants (AOSI) from 6 to 18 months. Diagnostic outcomes were determined at age 3 years blind to previous assessments. Results: Semiparametric group‐based modeling using AOSI scores identified three distinct trajectories: Group 1 ('Low', n = 435, 64.3%) was characterized by a low level and stable evolution of ASD signs, group 2 ('Intermediate', n = 180, 26.6%) had intermediate and stable levels, and group 3 ('Inclining', n = 61, 9.3%) had higher and progressively elevated levels of ASD signs. Among younger siblings, ASD rates at age 3 varied by trajectory of early signs and were highest in the Inclining group, membership in which was highly specific (94.5%) but poorly sensitive (28.5%) to ASD. Children with ASD assigned to the inclining trajectory had more severe symptoms at age 3, but developmental and adaptive functioning did not differ by trajectory membership. Conclusions: These prospective data emphasize variable early‐onset patterns and the importance of a multipronged approach to early surveillance and screening for ASD.